2015
DOI: 10.1002/bit.25902
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of acid resistance elements to improve acid resistance and propionic acid production of Propionibacterium jensenii

Abstract: Propionic acid (PA) and its salts are widely used in the food, pharmaceutical, and chemical industries. Microbial production of PA by propionibacteria is a typical product-inhibited process, and acid resistance is crucial in the improvement of PA titers and productivity. We previously identified two key acid resistance elements-the arginine deaminase and glutamate decarboxylase systems-that protect propionibacteria against PA stress by maintaining intracellular pH homeostasis. In this study, we attempted to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…In the proteomic study, some of the identified proteins such as LysE and secretory protein were directly or indirectly involved in amino acid metabolism (Guan et al, ); the importance of amino acid metabolism in P. acidipropionici acid tolerance and PA production was apparent in the metabolomic analysis (Guan et al, ). The roles of arginine deaminase (ADI) and glutamate decarboxylase (GAD) systems on acid resistance in P. acidipropionici have been confirmed repeatedly in microenvironmental analyses (Guan et al, ) and metabolic engineering (Guan et al, ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the proteomic study, some of the identified proteins such as LysE and secretory protein were directly or indirectly involved in amino acid metabolism (Guan et al, ); the importance of amino acid metabolism in P. acidipropionici acid tolerance and PA production was apparent in the metabolomic analysis (Guan et al, ). The roles of arginine deaminase (ADI) and glutamate decarboxylase (GAD) systems on acid resistance in P. acidipropionici have been confirmed repeatedly in microenvironmental analyses (Guan et al, ) and metabolic engineering (Guan et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…In our previous studies, the acid tolerance mechanism of P. acidipropionici was investigated at the levels of the microenvironment (Guan et al, ), proteins (Guan et al, ), and the metabolome (Guan et al, ). Additionally, acid‐resistance elements identified in these studies were engineered to improve the acid tolerance and PA production of P. jensenii (Guan et al, ). In this study, to further reveal the molecular mechanisms of acid tolerance and identify potential engineering targets, comparative genomic and transcriptomic analyses were conducted on wild‐type and acid‐tolerant P. acidipropionici .…”
Section: Introductionmentioning
confidence: 99%
“…[64] Genome editing, overexpression P. jensenii poxB or ldh knock-out and ppc overexpression Maximum 30% improvement in titre and 24% improvement productivity [65] Improve acid tolerance Overexpression P. acidipropionici otsA overexpression strain Propionic acid yield 11% higher. [66] Overexpression P. jensenii strains overexpressing gadB, arcA, arc, gdh or ybaS Up to a 1.5-fold increase in yield and 5.4-fold increase in titre, in shake flasks [67] Increase of metabolic flux towards propionate production Overexpression P. shermanii CoAT overexpression strain Increase yield and productivity, maximum 10% and 46%, respectively.…”
Section: Aim Strategy Strain Results Referencementioning
confidence: 99%
“…A novel approach for improving propionate production was explored by Guan et al by over-expressing acid resistance mechanisms in P. jensenii [67]. Compared to the strain harbouring an empty plasmid, over-expression of components of the arginine deiminase and glutamate decarboxylase systems typically improved the yield of propionate and the absolute titre reached in a glycerol media in shake-flasks.…”
Section: Gene Overexpressionmentioning
confidence: 99%
“…Two key acid resistance elements, the arginine deaminase and glutamate decarboxylase systems, have been identified and modified to improve acid resistance by 10 fold and even propionic acid production by 20% with regard to Propionibacterium jensenii [31].…”
Section: Biotechnological Productionmentioning
confidence: 99%